Economic Impact of Sacred Rituals: The Cyclical Relationship in the Towani Tolotang Community - Tarumingi, Denny Adri; Lopulalan, Dortje L. Y.; Zulkifli, Zulkifli; Kadir, Syahruddin (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2023)
This study investigates how the Towani Tolotang people express their religious and social values through traditional and special rituals related to their economy. This qualitative research utilises a phenomenological approach through observations, interviews, and literature studies. The findings reveal that the rituals performed by the Towani Tolotang community, such as Molalaleng, Mappaenre Inanre, Sipulung, and Mattampung, aim to obtain protection, happiness, and economic strength. These rituals involve offerings to DÄ“wata SeuwaE and are crucial in maintaining unity, harmony, and economic stability within the community. Through these rituals, which involve the use of new clothes and other economic activities, a significant contribution to the local economy is evident. The cultural identity displayed by the Towani Tolotang community encompasses positive values such as mutual respect, simplicity, and self-worth, which strengthen the nation's character and promote social harmony. This study contributes to understanding the socio-economic impact of traditional rituals and highlights the role of cultural practices in promoting economic resilience and social cohesion.